(3GdajhVGJ GdQHGfjI aj GdeBKQ GdbGOQjIs - (3ESeGYjd Hf eMeO SYjO GdbGOQjs
(3ChdgG (B:s
(3Gddge Efj Chef HeG JaYdg Cfg GdMbs
(3BNQgG (B:s
(3eG bQCfGg JMaI NGUI YGFOI YdjfG HQcGJg YGeI HQMeJc jG CQMe GdQGMejfs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs